Grassroots youth work : policy, passion and resistance in practice - De St. Croix, Tania (Policy Press, 2016)
This engaging book paints a picture of passionate grassroots youth workers, at a time when their practice is threatened by spending cuts, target cultures and market imperatives. Using interviews, dialogue and research diary excerpts the author brings youth work practice and theory to life.